Successful Treatment of Refractory and Relapsed CNS Acute Lymphoblastic Leukemia With CD-19 CAR-T Immunotherapy: A Case Report - Htun, Kyaw Thu; Gong, Qiang; Ma, Le; Wang, Ping; Tan, Ya; Wu, Guangsheng; Chen, Jieping (Frontiers in Oncology, 2021)
One important cause of treatment failure is extramedullary relapse among patients with acute lymphoblastic leukemia (ALL). This kind of infiltration is observed in the central nervous system. Chimeric antigen receptor-modified T cell therapy targeting CD-19 has shown to be a beneficial treatment approach in refractory and relapsed B cell acute lymphoblastic leukemia (r/r ALL). However, there is no much more studies reporting to treatment of refractory and relapsed B cell ALL in central nervous system.Here we reported one single case of a patient who has relapsed B cell ALL in CNS infiltration which was successfully treated by second generation, a CAR containing a co-st imulator CD28 or 4-1BB therapy. A 16- year old young adult male with refractory and relapsed B cell ALL in central infiltration was enrolled in a clinical trial. The patient got toxicity of grade 1 cytokine relapse syndrome and achieved significantly 36 months event free survival.This case of CAR-T treatment of relapsed and refractory ALL extramedullary central nervous system infiltration, successfully achieved 36 months disease-free survival. It is suggested that CD-19 CAR containing CD28 or 4-1BB costimulatory may be an effective method for clearing the infiltration of leukemia cells in the central nervous system. Its toxicity is mild and its safety is high.